Prevalence of laryngotracheal lesions in tracheostomized COVID-19 patients. A comparison with a matched historical control group of non-COVID-19 patients - Juan Manuel Carballo; Antonela Vicente; Ladislao Diaz Ballve; María Paula Pedace; Pablo Tocalini; Eliana Pérez Calvo; Karen Torres; Fernando Planells; Dario Villalba (European Clinical Respiratory Journal)
Objective To assess whether laryngotracheal lesions were more prevalent among tracheostomized post- coronavirus disease 2019 (COVID-19) adult patients compared with a matched historical control group of non-COVID-19 patients.Methods An analytical, observational, and cross-sectional study was conducted in a weaning and rehabilitation center. Our study was conducted on tracheostomized adult patients who underwent a fiberoptic bronchoscopy at admission. Non-COVID-19 patients of the historical control group were selected through propensity score (PS) matching. Each post-COVID-19 case was matched in a 1:1 ratio to a non-COVID-19 case. The PS was created based on age, days of endotracheal intubation before tracheostomy, days of artificial airway before bronchoscopy, and days of mechanical ventilation in intensive care unitResults Forty-nine matched patients were assessed in each group. The prevalence of airway lesions in post-COVID-19 patients and non-COVID-19 patients of the historical control group was 53.1% and 73.5%, respectively (p = 0.036). In the post-COVID-19 group, 12.2% had severe lesions, and in the historical control group of non-COVID-19 patients, 20.4%. The most prevalent lesion in both groups was granuloma, and lesions were most frequently localized in the subglottic region.Conclusions Our findings show a lower prevalence of laryngotracheal lesions in matched tracheostomized post-COVID-19 patients compared to a historical control group of non-COVID.The most prevalent lesion in both groups was mild (luminal obstruction < 50%) subglottic granuloma.